2020
DOI: 10.1111/bjh.16867
|View full text |Cite
|
Sign up to set email alerts
|

High‐fluorescent lymphocytes are increased in patients with COVID‐19

Abstract: High-fluorescent lymphocytes are increased in patients with COVID-19 Correspondence e76

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…The role of experimental CBC parameters and features available in the expanded CBC of many instruments has also been explored. For example, Wang et al have shown an increase of high fluorescent lymphocytes (HFL) using the Sysmex XE‐5000 blood cell counter, compared to healthy subjects 47 . Gérard et al have found that 5%‐10% of FBC from COVID‐19 patients were flagged by the blood cell counters (MO flag for the Beckman‐Coulter DxH 800 and Blasts/AbnLymphs for the Sysmex X10) and required peripheral blood film assessment 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of experimental CBC parameters and features available in the expanded CBC of many instruments has also been explored. For example, Wang et al have shown an increase of high fluorescent lymphocytes (HFL) using the Sysmex XE‐5000 blood cell counter, compared to healthy subjects 47 . Gérard et al have found that 5%‐10% of FBC from COVID‐19 patients were flagged by the blood cell counters (MO flag for the Beckman‐Coulter DxH 800 and Blasts/AbnLymphs for the Sysmex X10) and required peripheral blood film assessment 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Many papers have indicated that, besides lymphocytopenia, neutrophilia is an outstanding feature of COVID‐19, especially in patients with severe disease 1,47,49,63 . Several groups have described aspects of disorderly granulopoiesis, generally considered as associated (as a co‐cause or as an effect) with inflammation and cytokine storm or, in a minority of studies, with bacterial superinfections.…”
Section: Discussionmentioning
confidence: 99%
“…As described by Martens et al [1], the XN-series analysers (Sysmex, Kobe, Japan) can differentiate leukocytes according to their light scatter and fluorescence properties, providing information relating to intracellular complexity (SSC), nucleic acid content (SFL), and cellular size (FSC). In patients with COVID-19, Martens et al [1] observed an increase in reactive, antibody-synthesizing, and high-fluorescence lymphocytes consistent with the lymphocyte-centric approach to COVID-19 monitoring in the literature [5]. However, Martens et al [1] also noted significant changes in the haemocytometrics of all circulating blood cells in patients with COVID-19 who developed cytokine-storm syndrome, paying particular attention to the increased proportion of activated monocytes.…”
Section: To the Editormentioning
confidence: 78%
“…Notably, the reduced B cells were related to the prolongation of viral RNA shedding from respiratory tract in COVID-19 patients ( Hao et al, 2020 ). Interestingly, high fluorescent lymphocytes (HFL) associated with activated B cells or plasma cells were elevated in COVID-19 patients ( Wang Z. et al, 2020 ). HFL tended to increase as the disease progressed, which might promote the production of plasma cells and specific antibodies in patients.…”
Section: Pathogenicity Of Sars-cov-2mentioning
confidence: 99%
“…Actually, SARS-CoV-2 infected T lymphocytes through membrane fusion mediated by S protein, which could be inhibited by EK1 peptide (Wang X. et al, 2020). However, SARS-CoV-2 could not replicate in MT-2 cells.…”
Section: Lymphocyte Dysregulationmentioning
confidence: 99%